Trade competitiveness and sustainability policies of Malaysian Palm Oil in the European Union: strategic responses by stakeholders agencies - Lakshmy Naidu,; Mohd Ikbal Mohd Huda,; Ravichandran Moorthy, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Malaysian palm oil industry is a significant contributor towards national development and economic growth. However, the industry has been facing rising tension to ensure sustainable development, as global demand for palm oil continue to grow in the coming years. The necessity for producing and trading sustainably produced palm oil is amplified with the European Union’s stringent requirement for importing responsibly sourced commodities into its market, with the aim to achieve climate-neutral by 2050. The palm oil industry is also inundated with anti-palm oil campaigns and agendas, which emphasize allegations of unsustainable agricultural practices as large-scale plantations damage the natural ecosystem in producing countries. Collectively, these challenges could pose a formidable impact on the trade of palm oil between Malaysia and the European Union. Therefore, the article seeks to examine the strategic responses undertaken by Malaysian stakeholder agencies to address the regulations pertaining to sustainable production of palm oil. Using a qualitative approach, a total of ten sessions of in-depth interviews were held with expert informants in stakeholder agencies, both in Malaysia and the European Union. Among the key findings were the formulation and implementation of the National Agricommodity Policy, deployment of various missions to the European Union, implementation of Malaysian Sustainable Palm Oil (MSPO) certification as the national sustainability scheme, dissemination of accurate information on sustainable and certified palm oil, and continuous engagement through bilateral and multilateral platforms. Based on the findings, this study suggests that inclusive and transparent engagement must be conducted continuously. Constantly held dialogue sessions will help to promote better understanding and fruitful collaboration among stakeholder agencies in Malaysia and the European Union to balance environmental concerns with trade interests.